FARMERS’ PERCEPTION OF THE ATTRIBUTES OF SELECTED POTATO TECHNOLOGIES* - Kumar, Anil (Potato Journal, 2013)
Farmers’ perception of the attributes of any agricultural technology is the key determinant to its final adoption. The present study was conducted in Shimla district to assess the attributes of potato technologies pertaining to the management of early and phoma blight, and cutworms. A total of 75 farmers from 15 villages of Rampur-Keonthal and Baghi panchayats were selected randomly for the study. Seven attributes of potato technologies were assessed and the results showed that the farmers perceived the potato technologies as having high degree of simplicity, medium degree of compatibility, high degree of observability, high degree of divisibility, low cost requirement, medium level of profitability and high degree of predictability. The overall attributes of the potato technologies were perceived as favourable by the farmers.